An Evaluation on Ibrahim Madkur’s Critical Text Edition of Ibn Sina’s Ash-Shifa’ - Fathan Aniq, Ahmad (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2022)
Ibn SÄ«nÄ is one of the prominent scholars in the Muslim scientific world. In the West, he is well known as Avicenna. As a polymath, he wrote many books in a broad range of sciences. Al-QÄnÅ«n fÄ« aá¹-Tibb (the Canon of Medicine) and KitÄb Ash-ShifÄâ€™ (the Boook of Healing) are considered to be his magnum opuses. While the former is his greatest work on medicine, the latter is his monumental contribution to science and philosophy. KitÄb Ash-ShifÄâ€™ is concerned with four main subjects: logic (al-maná¹iq), natural sciences (aá¹-á¹abiâ€™iyÄt), mathematics (ar-Riyaá¸iyÄt), and metaphysics or theology (al-IlÄhiyÄt).